Myasthenia Gravis Development and Crisis Subsequent to Multiple Sclerosis - Gharagozli, Kurosh (Hindawi Publishing Corporation, 2011)
During the last decade, sporadic combination of multiple sclerosis (MS) and myasthenia gravis (MG) has been reported repeatedly. Although these are anecdotal, they are important enough to raise concerns about co-occurrence of MG and MS. Here, we present a case of an MS patient who developed an MG crisis. She had received interferon for relapsing remitting MS. Interestingly, she developed an MG crisis 4 years after the diagnosis of MS. MS and MG have relatively the same distribution for age, corresponding to the younger peak of the bimodal age distribution in MG. They also share some HLA typing characteristics. Furthermore, some evidences support the role of systemic immune dysregulation due to a genetic susceptibility that is common to these two diseases. The association may be underdiagnosed because of the possible overlap of symptoms especially bulbar manifestations in which either MG or MS can mimic each other, leading to underestimating incidence of the combination. The evidence warrants physicians, especially neurologists, to always consider the possibility of the other disease when encountering any patients either with MS or MG. Anecdotal and sporadic reports of combination of multiple sclerosis (MS) and myasthenia gravis (MG) have been raised concerns about co-occurrence of them.